JURIDICAL DESIGN OF REGIONAL ACCOUNTABILITY IN DISASTER MANAGEMENT BASED ON THE WELFARE STATE PERSPECTIVE - Andara Tsabitha; Arif Hidayat (Law Research Review Quarterly, 2026)
This study analyzes the juridical design of regional accountability in disaster management from a welfare state perspective. It examines the accountability system of regional governments based on existing regulations and evaluates its effectiveness. Using a normative juridical method with statute, conceptual, and comparative approaches, the study finds that although the legal framework is formally adequate, its implementation remains administrative and not fully effective. Based on Mark Bovens' theory, weaknesses are found in the lack of measurable indicators, unclear accountability mechanisms, limited public participation, and weak coordination. From a welfare state perspective, the system has not fully ensured the protection of citizens' rights and public welfare. Therefore, strengthening regulations, coordination, and performance-based accountability is necessary.